PENGARUH PEMBIAYAAN MUSYÄ€RAKAH TERHADAP TINGKAT PROFITABILITAS BANK UMUM SYARIAH TAHUN 2017-2019 - lutfiah, sulfiana; Novianty, Rina (Faculty of Islamic Economics and Business, 2022)
This study aims to examine the effect of musyÄrakah financing on the profitability level of Islamic commercial banks and how much it affects the three-year period through published report data. This study consists of two variables, namely the independent variable which is mÅ«rÄbahah financing and the dependent variable is the level of profitability. Type of research using quantitative research. The data source in this study is a secondary data source from Islamic commercial banks in the period 2017 to 2019 and analyzed by panel data regression. Based on the results of data testing in the combined test, the effect of musyÄrakah financing on profitability shows a probability value (X) of 0.0038 where < 0.05, then the hypothesis is accepted. So musyÄrakahini financing has a significant effect on the profitability of the three Islamic commercial banks that have been studied, namely Bank Mega Syariah, Bank BCA Syariah, and Bank Syariah Bukopin.